Confined, Controlled, and Violated: The Rohingya Women in Bangladesh Refugee Camps - Ena Tripura (Feminist Encounters: A Journal of Critical Studies in Culture and Politics, 2022)
Encampment of the Rohingyas in the camps in Bangladesh has reinforced the continuum of male dominance and violence carried out on women’s bodies. This article employs Judith Butler’s concepts of precarious life and frames of recognition to analyse three layers of violence against Rohingya refugee women: the violence carried out by the humanitarian regime, by Rohingya men as spaces to express their anger and frustrations, and by local Bangladeshi men as sites to demonstrate their superiority over the Rohingya intruders into the national space. The article draws on secondary literature on Rohingya refugees’ lived experiences in camps and semi-structured interviews conducted with humanitarian service providers.